HAKIM PEREMPUAN SEBAGAI TRANSFORMATION AGENT DALAM PERSPEKTIF FEMINISME ISLAM - Rahmat Gilang Ramadhan (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2025)
This study aims to examine the role of female judges in Islamic courts in Indonesia and how their presence influences gender justice in legal practice. The research addresses the question: How do female judges contribute to more inclusive and equitable interpretations of Islamic family law? A qualitative normative approach with conceptual and comparative methods was employed to analyze legal texts, court decisions, and relevant literature. The results indicate that female judges tend to apply relational justice and empathy in their decision-making, particularly in cases involving gender issues. Despite facing structural and cultural challenges, such as persistent gender stereotypes, female judges have made significant contributions to the reform of Islamic family law. The impact of these findings shows that adopting an Islamic feminist perspective enables legal interpretations that are more responsive to societal needs. Strengthening the competencies of female judge candidates and integrating feminist perspectives into legal education are recommended strategies to enhance gender justice in the judicial system. This research demonstrates that empowering female judges positively influences fairer, socially responsive legal outcomes